Should An Early Hospital Discharge Strategy Be Implemented Following A Successful Primary PCI For Acute ST Elevation Myocardial Infarction? - Koren, Ofir; Mahamid, Mohamad; Rozner, Ehud; Hakim, Rony; Turgeman, Yoav (Cardiology and Cardiovascular Medicine, 2019)
Background: Early hospital discharge following ST elevation myocardial infarction and primary PCI is reasonable after 72 hours for selective low risk patients. Yet, these recommendations, which were mainly based on data from, are not widely implemented. We present a single center experience regarding efficacy and safety of early hospital discharge. Method: We conducted a retrospective study based on data from 2014 to 2015. The patients were classified into three groups based on the duration of hospitalization; within 48 h, 48–72 h, and >72 h. The primary endpoints were all-cause mortality and major cardiovascular events (MACE) within 30 days and at 1 year. Secondary endpoint was a diagnosis of acute kidney injury. Results: 178 patients were included; 60 patients (33.7%) were discharged within 48 hours, 75 patients (42.1%) were discharged after 72 hours, and 43 patients (24.2%) were discharged between 48 and 72 h. Patients discharged >72 h were significantly older (p <0.001), had extensive myocardial damage (p < 0.001) and a significant reduction in left ventricular systolic function (p < 0.02). Most common catheterization approach in this group was the femoral artery (p < 0.02). No statistically significant difference was observed between the three regarding primary and secondary. Conclusion: Early hospital discharge, within 48 to 72 hours after successful primary PCI for Acute STEMI was not associated with a higher rate of all-cause mortality or MACE up to one year after discharge for selected patients. In an era where the incidence of and mechanical complications are low an early hospital discharge strategy should be widely and routinely implemented.